Coke formation during thermal cracking of a heavy crude oil (2015)
A pseudo-mechanism for the production of coke during the thermal cracking of a Colombian heavy crude oil was proposed based on thermal cracking experiments carried out at TGA and at horizontal tube furnace at atmospheric conditions. In-situ combustion (ISC) is a thermal method that improves the recovery of heavy crude oils and involves complex phenomena such as heat and mass transfers, low-temperature oxidation of the liquid phase (LTO), and cracking reactions that yield coke, a carbonaceous residue that, after high-temperature oxidation (HTO) produces the heat that reduces the oil viscosity increasing the recovery factor. During cracking experiments, Ottawa sand was mixed with crude oil, or with a mixture of maltenes and asphaltenes extracted from that oil, and placed under nitrogen atmosphere and heated at 2oC/min up to di_erent reaction temperatures (300oC, 350oC, 400oC and 450oC) at atmospheric pressure conditions. Even tough atmospheric pressure conditions is not a realistic condition as oil reservoirs operate above atmospheric pressure, this study as part of a bigger project to study ISC it was the _rst that develop a setup and a methodolody able to study ISC reactions. After the _rst approximation that this study made, further work will be carried out to study ISC process at more realistic conditions. This study found that the main cracking products were volatiles that could be condensables and non-condensables and a solid residue. Proximate, elemental, GC-MS and SIMDIS analysis were performed to establish the composition of the cracking products, and to determine the advance in the cracking reactions. During cracking experiments each oil fraction yielded lower- and heavier-molecular weight products. e.g. maltenes yielded gas (mainly composed by methane CH4), distillables (a condensable fraction with maximum 18 carbons), low-molecular-weight maltenes (LMWM, a condensable fraction with maximum 28 carbons, that results from the cracking of maltenes and asphaltenes), and asphaltenes. Whereas asphaltenes leaded to coke formation and to LMWM and gases. The proposed pseudo-mechanism considers the formation of lower- and heavier molecules, separates the evaporation process from the thermal cracking, and proposed new pseudocomponents such as Maltenes* that represents the maltenes fraction after the evaporation process and the one available for thermal cracking, and LMWM that is an upgraded cracking product of the cracking of maltenes* and asphaltenes that had a yield of 0.28 g/gtot. Furthermore, the proposed pseudo-mechanism proposes kinetic parameters for the thermal cracking of a Colombian heavy crude oil under in-situ combustion conditions at atmospheric pressure. The kinetic parameter were optimized by minimizing the sum of square error (SSE) between the experimental and calculated yields. A good coe_cient of determination was obtained, (R2=0; 97), using _rst order kinetic parameters. The physical interpretation of the value of kinetic parameters is complicated given the rather empirical approach used to find the kinetic parameters, it is important to note that most parameters in particular activation energies have values typical for chemical-controlled process, exceptions to this are the activation energies 26.4 and 9760 kJ/mol that are too low and too high that involve the decomposition of asphaltenes and are accompained by very low pre-exponential factor.Future work may focus on reducing the empirical nature of this mechanism.